2001
DOI: 10.1093/ndt/16.7.1459
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term CAPD patients are volume expanded and display more severe left ventricular hypertrophy than haemodialysis patients

Abstract: Left ventricular hypertrophy is more severe in long-term CAPD patients than in HD patients. This finding is associated with evidence of more pronounced volume expansion, hypertension, and hypoalbuminaemia. Volume and pressure load along with factors associated with hypoalbuminaemia may aggravate LVH in uraemic patients on CAPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
6
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 20 publications
8
139
6
2
Order By: Relevance
“…There is a need for further research in this area, especially given that LVH is more common amongst long-term PD patients compared to haemodialysis patients. 55 …”
Section: What Is the Evidence-base Amongst Peritoneal Dialysis Patients?mentioning
confidence: 99%
“…There is a need for further research in this area, especially given that LVH is more common amongst long-term PD patients compared to haemodialysis patients. 55 …”
Section: What Is the Evidence-base Amongst Peritoneal Dialysis Patients?mentioning
confidence: 99%
“…Anemia, mineral and bone disorders, the inflammation-muscular-wasting complex, cardiomyopathy, neuropathy, and depression, all disturbances that frequently coexist in CKD-5D, may be involved in the poor physical functioning of this population (3)(4)(5)(6). Pulmonary congestion detected and quantified by lung ultrasonography recently emerged as a powerful correlate of poor physical functioning in a multicenter study in peritoneal dialysis (PD) patients (7), a population with an exceedingly high prevalence of fluid overload and left ventricular dysfunction (8)(9)(10), suggesting that volume expansion and cardiomyopathy, two potentially reversible risk factors, play a major role in the poor physical performance of this population.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, these studies showed clearly that IDH was an independent subtype of hypertension in clinics. It should be noted that certain indices of fluid status, such as the cardiac and thoracic ratio (CTR), Vena Cava diameter or atrial natriuretic peptide levels, would have contributed greatly to the present analysis, had they been available, since fluid overload is widely recognized to play an important role in the pathogenesis of hypertension in dialysis patients (36). A previous study has shown that fluid overload is very common in dialysis patients (36), and hypertensive dialysis patients usually have more extracellular water than normotensive dialysis patients (37).…”
Section: Isolated Diastolic Hypertension: An Independent Subtype Of Hmentioning
confidence: 99%
“…It should be noted that certain indices of fluid status, such as the cardiac and thoracic ratio (CTR), Vena Cava diameter or atrial natriuretic peptide levels, would have contributed greatly to the present analysis, had they been available, since fluid overload is widely recognized to play an important role in the pathogenesis of hypertension in dialysis patients (36). A previous study has shown that fluid overload is very common in dialysis patients (36), and hypertensive dialysis patients usually have more extracellular water than normotensive dialysis patients (37). Whether fluid status also has some effect on aortic stiffness is not clear at present, but we believe that the availability of these indices would help us to understand more, if not all, about the underlying mechanism of the present findings.…”
Section: Isolated Diastolic Hypertension: An Independent Subtype Of Hmentioning
confidence: 99%